VERBAL PHRASES IN THE NOVEL LIFE OF PI: A SYNTACTIC ANALYSIS - Syafrizal Syafrizal (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study is intended to find out the types and functions of verbal phrases used in the novel Life of Pi. This research belongs to descriptive qualitative research, where the data are not analyzed by using statistical procedure; the data in this research are taken from the novel Life of Pi by Yann Martel. To collect the data the writer uses the noting technique. The first step, the writer read and observed carefully to find out the verbal phrases. Then, the writer took notes of the sentences contained verbal phrases in Life of Pi, and then analyzed the data by classifying the verbal phrases and finding the function of verbal phrases. The research finding shows that there are three types of verbal phrases used in the novel Life of Pi, namely, gerund phrase, infinitive phrase, and participial phrase. Each type of verbal phrases has a different function. The researcher finds three functions of verbal phrases, namely noun, adjective, and adverb. Gerund phrase functions as a noun. Infinitive phrase functions as a noun, an adjective, and an adverb. Participial phrase functions as an adjective and as an adverb.